Multiple behavioral factors are associated with occurrence of large, flat colorectal polyps - Zhan, Tianzuo; Hahn, Felix; Hielscher, Thomas; Bilge, Asmé; Betge, Johannes; Gaiser, Timo; Kähler, Georg; Ebert, Matthias; Belle, Sebastian (International journal of colorectal disease, 2017)
PurposeThe prevalence of advanced dysplasia and synchronous lesions is particularly high in patients with large, flat colorectal polyps. However, the impact of lifestyle on the development of such polyps is poorly investigated. Hence, this study aims to identify associations between behavioral factors and the occurrence of large, flat colorectal polyps.MethodsBehavioral factors were retrospectively analyzed in patients with large, flat polyps and control patients with at most one diminutive polyp. Information on lifestyle factors, comorbidities, and demographic parameters were determined by a structured, self-administered questionnaire.ResultsQuestionnaires of 350 patients with large, flat polyps and 489 control patients were included in the analysis. Most large, flat colorectal polyps contained adenoma with low-grade neoplasia and were located in the right colon. Multivariate analysis showed that advanced age (per 1-year increase—OR 1.09, CI 1.07-1.11, p < 0.0001), frequent cigarette smoking (OR 2.04, CI 1.25-3.32, p = 0.0041), daily consumption of red meat (OR 3.61, CI 1.00-12.96, p = 0.0492), and frequent bowel movements (OR 1.62, CI 1.13-2.33, p = 0.0093) were independent risk factors for occurrence of large, flat colorectal polyps. In contrast, frequent intake of cereals (OR 0.62, CI 0.44-0.88, p = 0.0074) was associated with a reduced risk.ConclusionMultiple behavioral factors modulate the risk for developing large, flat colorectal polyps. This knowledge can be used to improve prevention of colorectal cancer.
Published online: 28 November 2016
Gesehen am 30.07.2018